Association between skin flap thickness and Frey's syndrome in parotid surgery. Issue 12 (8th March 2013) - Durgut, Osman; Basut, Oguz; Demir, Uygar Levent; Özmen, Ömer A.; Kasapoglu, Fikret; Coskun, Hakan
<x xml:space="preserve">Abstract</x> Background Frey's Syndrome is a frequent complication of parotid surgery. The aim of this study was to evaluate the association between skin flap thickness and Frey's Syndrome in patients who underwent superficial parotidectomy. Methods Thirty adult patients were randomized into 2 groups: subcutaneous and subsuperficial musculoaponeurotic (sub‐SMAS) skin elevation. In both groups skin flap thickness was measured by a micrometer at defined points. The patients were queried for subjective Frey's Syndrome and Minor's test was performed for objective Frey's Syndrome. Results The thickness of skin flap in the subcutaneous group was significantly less than that in the sub‐SMAS group. There was no statistical significance between skin flap thickness and objective Frey's Syndrome, although the dimension of the colored area in the subcutaneous group was larger compared with that of the sub‐SMAS group: 7.5 cm2 (0–48 cm2) and 0.5 cm2 (0–18 cm2), respectively. Conclusions In conclusion, sub‐SMAS elevation of the skin flap in parotid surgery provides better results regarding Frey's Syndrome. © 2013 Wiley Periodicals, Inc. Head Neck 35: 1781–1786, 2013